Effects of sodium caseinate on hindgut fermentation and fiber digestion in horses. (13th December 2018) - Jordan, Katie V; Drouillard, James S; Douthit, Teresa L; Lattimer, James M
Abstract: Eight cecally cannulated Quarter Horses were used in a replicated 4 × 4 Latin square experiment conducted in four 14-d periods to determine effects of sodium caseinate (casein) on hindgut fermentation and fiber digestion. During each period, horses were assigned to one of four treatments consisting of control (water; CON ), 0.125 g casein/kg BW (LOW ), 0.25 g casein/kg BW (MED ), or 0.5 g casein/kg BW (HI ). Casein was solubilized in 800 mL water and dosed directly into the cecum at 0700 and 1900 hours using a metal dosing syringe. Smooth Bromegrass hay (CP 8.50%), water, and salt were provided ad libitum. New hay was fed at 0700 and 1900 hours, and orts were recorded at 1900 daily. During the final 3 d of each period, cecal digesta were collected every 6 h, pH was measured, and samples were frozen for subsequent analyses of VFA and NH3 concentrations. Feed intake during the final 4 d of each period was recorded. Feces were collected during the 3-d sampling period, pooled, subsampled, and frozen. Fecal samples were analyzed for pH and used to determine digestibilities of DM, OM, NDF, and ADF. Statistical analyses were performed via the GLIMMIX procedure of SAS 9.4. Linear and quadratic effects of sodium caseinate on pH, VFA concentrations, and apparent digestibility were assessed by SAS. Digestibilities of DM, OM, ADF, and NDF were unaffected by treatment ( P > 0.40). Horses dosed with CON and MED treatments had greater cecal pH than those fed LOW or HI treatments ( P < 0.01). Cecal NH3 concentrations increased linearly in response to the amount of casein administered ( P < 0.01). Cecal NH3 decreased 6 h after dosing and addition of new hay, regardless of treatment ( P < 0.01). Total cecal VFA were unaffected by treatment ( P > 0.10), but VFA changed over time with the greatest concentrations observed 6 h after treatments were administered and introduction of new hay ( P < 0.01). Treatment did not affect DMI ( P ≥ 0.17). In this experiment, cecal infusions of sodium caseinate had minimal to no effect on fermentation parameters or fiber degradation in the horse. A type II error may have occurred due to small population size or the medium quality hay fed to these horses provided sufficient N for microbial fermentation.